Parental Awareness of the Philippine K to 12 Curriculum: A Basis for an Intensive Orientation Scheme - Gomez, Aurelio Jr., S. (Journal of Social Work and Science Education, 2025)
This study was conducted to determine the level of awareness of parents on the K to 12 curriculums. The results of the investigation served as the basis for an intensive orientation scheme. This study utilized mean, t-tests for uncorrelated samples, and analysis of variance. The respondents of this study were the 150 parents of the Grade 1 pupils of Talomo District, Division of Davao City, for the School Year 2013-2014 who were chosen through purposive sampling technique. In the absence of standardized instruments, the researcher employed a researcher-made instrument in the form of a checklist with three options. The study revealed that the level of awareness of parents on the K to 12 curriculum is moderate. It is ascertained in this study that there is no significant difference in the level of awareness of parents on the K to 12 curriculums when analyzed by gender, family income, nature of work, and educational attainment. The null hypothesis, which stated that there is no significant difference in the level of awareness of parents on the K to 12 curriculums when analyzed by gender, family income, nature of work, and educational attainment, was accepted. In light of the findings of the study, an orientation scheme for parents on the K to 12 curriculum is proposed. It is recommended that schools continue to communicate to the community the innovations in the educational systems by holding fora in order to make the community aware of the programs, which can help in the implementation of the curriculum. The Department of Education (DepED) shall continue to monitor the orientation mechanism done by the schools on the implementation of the K to 12 curriculums. It is also endorsed to implement the orientation scheme on the K to 12 curriculums designed by the researcher. Further, it is recommended to conduct another study on the level of awareness of stakeholders on the K to 12, like the industries, local government units, and civil societies.